1997
DOI: 10.1523/jneurosci.17-22-08778.1997
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Overexpression of the Neurite Growth-Associated Protein B-50/GAP-43 in Cerebellar Purkinje Cells Induces Sprouting after Axotomy But Not Axon Regeneration into Growth-Permissive Transplants

Abstract: B-50/GAP-43 is a nervous tissue-specific protein, the expression of which is associated with axon growth and regeneration. Its overexpression in transgenic mice produces spontaneous axonal sprouting and enhances induced remodeling in several neuron populations (Aigner et al., 1995;Holtmaat et al., 1995). We examined the capacity of this protein to increase the regenerative potential of injured adult central axons, by inducing targeted B-50/GAP-43 overexpression in Purkinje cells, which normally show poor regen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
105
0
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 117 publications
(119 citation statements)
references
References 58 publications
13
105
0
1
Order By: Relevance
“…Injection of anti-Nogo-A antibodies in the cerebellar cortex induces sprouting from Purkinje axons in the granular layer (Buffo et al, 2000), and a similar phenomenon is observed after injury in GAP-43 (growthassociated protein-43)-overexpressing Purkinje cells (Buffo et al, 1997;Gianola and Rossi, 2004). In both conditions, in addition to the outgrowth of terminal fibers from the infraganglionic plexus, sprouting also occurs along the corticofugal neurite, and this phenomenon may be accompanied by disruption of the normal axon-myelin relationship (Gianola and Rossi, 2004).…”
Section: Effects Of Cspgs Degradation On Axon Myelinationmentioning
confidence: 76%
“…Injection of anti-Nogo-A antibodies in the cerebellar cortex induces sprouting from Purkinje axons in the granular layer (Buffo et al, 2000), and a similar phenomenon is observed after injury in GAP-43 (growthassociated protein-43)-overexpressing Purkinje cells (Buffo et al, 1997;Gianola and Rossi, 2004). In both conditions, in addition to the outgrowth of terminal fibers from the infraganglionic plexus, sprouting also occurs along the corticofugal neurite, and this phenomenon may be accompanied by disruption of the normal axon-myelin relationship (Gianola and Rossi, 2004).…”
Section: Effects Of Cspgs Degradation On Axon Myelinationmentioning
confidence: 76%
“…GAP43 has an important role in promoting neurite outgrowth 23,24,55 but it is not a survival factor per se, indeed prolonged over-expression of GAP43 in other CNS neurons can sometimes induce cell death. 60 …”
Section: Cntf Gene Therapy and Visual System Repair Sg Leaver Et Almentioning
confidence: 99%
“…The involvement of GAP-43 in neuronal structural plasticity was demonstrated in many studies based on gene depletion or overexpression of its wild-type or mutated variants in cultured cells and transgenic mice (21,22). GAP-43 overexpression is sufficient to induce neurite formation and axonal sprouting in different regions of adult CNS (21,23,24).…”
mentioning
confidence: 99%